The Presumptive Tax Regime on Micro, Small and Medium Enterprises in Indonesia - Aditya, Chandrika (CV. Ridwan Publisher, 2020)
In July 2013, Indonesia implemented the presumptive tax regime on micro, small and medium enterprises (MSMEs) by assigning Government Regulation No.46/2013. This regulation simplified the tax administration and provides tax cuts to MSMEs to help them grow and encourage voluntary tax compliance, which eventually will increase their contribution to state revenue. This study provides an analysis of the implementation of this new tax regime by comparing related literature on practices of this tax regime in many countries with the recent conditions in Indonesia after this regulation was applied. It seems that the new tax regime encourages voluntary tax compliance and stimulates the contribution of MSMEs to state revenue. However, some challenges, such as different definitions, lack of tax knowledge, impartiality to business losses, and the indication of tax avoidance must be overcome by the government by improving policies that favor MSMEs. Keywords: Indonesia, MSMEs, presumptive tax, threshold